Promoting schoolchildren's self-esteem in physical education: testing the effectiveness of a five-month teacher training. (3rd July 2020) - Rubeli, Benjamin; Oswald, Esther; Conzelmann, Achim; Schmid, Jürg; Valkanover, Stefan; Schmidt, Mirko
ABSTRACT: Background : Schoolchildren's personality development is considered a central goal of physical education (PE). With regard to the relationship between psychological well-being and global self-esteem over the life course, the promotion of positive self-esteem is an issue of particular significance. Past research revealed that PE taught with an individualized teacher frame of reference (iTFR) and a reflexive teaching style is associated with positive effects on facets of children's perceived sports competence. However, it remains an open question whether this teaching styles has the potential to promote positive self-esteem. Purpose : The present study investigated whether a five-month teacher training, aimed to enhance the teachers' iTFR and their reflexive teaching style in PE, has a positive effect on students' perceived sports competence and their global self-esteem. To analyse the implementation quality, changes in students' perceived iTFR and perceived reflexive teaching style were investigated. Method : A total of 21 teachers were assigned to either an intervention group ( n = 13), receiving the five-month teacher training, or a control group ( n = 8) consisting of regular teaching without teacher training. The teacher training encompassed five three-hour consecutive sessions during which the teachers acquired theoretical and practical knowledge about the promotion of competence perceptions in PE with a reflexive teaching style and an iTFR. Between the sessions, the teachers were instructed to implement an iTFR and a reflexive teaching style into their own PE classes. To evaluate the effects of the teacher training, their students' ( N = 315, 53.7% girls, M age = 13.2 y, SD age = 1.3 y) perceived teaching style (iTFR and reflexive teaching), perceived sports competence and global self-esteem were measured with paper-pencil questionnaires at three measurement points (pre, post and follow-up). Findings : Linear mixed effect models showed that students of the intervention group reported an increase in their teachers' reflexive teaching style, but there were no changes with regard to iTFR. With regard to students' perceived sports competence and global self-esteem, there were significant interaction effects between time and group over a period of eight months (from pre-test to follow-up), indicating positive effects on these self-concept dimensions due to the teacher training. Conclusion : The present study indicates that a long-term teacher training supports PE teachers to implement teaching styles with the aim to promote students' self-concept. Furthermore, the findings lead to the assumption that a more pronounced iTFR in combination with an enhanced reflexive teaching style has the potential to positively influence schoolchildren's perceived sports competence and global self-esteem.